Determining the season of death from the family composition of insects infesting carrion - Moretti, Thiago de Carvalho [UNESP]; Bonato, Vinicius; Conde Godoy, Wesley Augusto (Czech Acad Sci, Inst Entomology, 2011)
Determining the season of death by means of the composition of the families of insects infesting carrion is rarely attempted in forensic studies and has never been statistically modelled. For this reason, a baseline-category logit model is proposed for predicting the season of death as a function of whether the area where the carcass was exposed is sunlit or shaded and of the relative abundance of particular families of carrion insects (Calliphoridae, Fanniidae, Sarcophagidae, and Formicidae). The field study was conducted using rodent carcasses (20-252 g) in an urban forest in southeastern Brazil. Four carcasses (2 in a sunlit and 2 in a shaded area) were placed simultaneously at the study site, twice during each season from August 2003 through June 2004. The feasibility of the model, measured in terms of overall accuracy, is 64 +/- 14%. It is likely the proposed model will assist forensic teams in predicting the season of death in tropical ecosystems, without the need of identifying the species of specimens or the remains of carrion insects.
Keywords: Forensic science; forensic entomology; necrophagous insects; seasonal dating; seasonality; Calliphoridae; Sarcophagidae; Fanniidae; Formicidae; baseline-category logit model